A non-phosgene process for bioderived polycarbonate with high molecular weight and advanced property profile synthesized using amino acid ionic liquids as catalysts. Issue 8 (3rd April 2020) - Zhang, Zhencai; Xu, Fei; Zhang, Yaqin; Li, Chenhao; He, Hongyan; Yang, Zifeng; Li, Zengxi
Abstract : Bio-based polycarbonate with high molecular weight and advanced property profile was synthesized using amino acid ionic liquids as catalysts. Abstract : The conversion of biomass and carbon dioxide to plastics is one of the key solutions to reduce the greenhouse effect and alleviate the petroleum resource depletion. However, there is still a lack of bioderived polymers with high molecular weights and excellent performance and their corresponding green synthesis processes, which limits the potential of bioderived polymers to replace petroleum-based polymers. In this study, an eco-friendly synthetic process for bioderived polycarbonate, catalyzed by amino acid ionic liquids, was developed by utilizing isosorbide (ISO) and diphenyl carbonate (DPC) as reactants, derived from a renewable resource and carbon dioxide, respectively. By using 1-ethyl-3-methylimidazole lysine ([Emim][Lys]) as a catalyst, poly(isosorbide carbonate) (PIC) with the weight average molecular weight of 150 000, the highest reported so far to the best of our knowledge, was synthesized, and the T g of PIC was up to 174 °C. The reaction mechanism was investigated using nuclear magnetic resonance (NMR) spectroscopy, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF MS), and density functional theory (DFT) calculation. The remarkable catalytic performance was attributed to the fact that [Emim][Lys] could effectively activate the hydroxyl group of ISO and carbonyl group of DPC, and inhibit the formation of cyclic intermediates. Moreover, to overcome the brittleness of PIC, 1, 4-butanediol (BD) and 1, 4-cyclohexanedimethanol (CHDM) were introduced into PIC, and the copolycarbonate showed excellent Young's modulus, ultimate tensile strength, and elongation at break, which were 979 MPa, 57 MPa, and 145%, respectively, and were comparable to the commercial petroleum-based polycarbonates. Such a process provides further industrial prospects for the next generation of bioderived polycarbonate.